Pengaruh Media Arang Sekam Padi Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis Guineensis Jacq) di Pre Nursery - Andi Eviza; Amaliyah Syariyah; Dawan Romadan (SINTA Journal (Science, Technology, and Agricultural), 2025)
This study aimed to determine the effect of rice husk charcoal on the growth of oil palm (Elaeis guineensis Jacq) seedlings in a pre-nursery. This study was conducted at the Experimental Garden of the Payakumbuh State Agricultural Polytechnic for four months, from March to June 2025, using a Completely Randomized Design (CRD) with five treatments and five replications. Treatment variations consisted of the ratio of topsoil to rice husk charcoal: P1 (1 topsoil: 1 rice husk charcoal), P2 (1 topsoil: 2 rice husk charcoal), P3 (1 topsoil: 3 rice husk charcoal), P4 (2 topsoil: 1 rice husk charcoal), and P5 (3 topsoil: 1 rice husk charcoal). Observed parameters included seedling height, number of leaves, stem diameter, length of the widest leaf, and width of the widest leaf. The results showed that the P2 treatment significantly affected seedling height (22.30 cm), leaf length (16.84 cm), and leaf width (5.12 cm), but had no significant effect on leaf number or stem diameter. The P2 media mixture is recommended as the optimal pre-nursery growing medium for the initial growth of oil palm seedlings.